Simulasi Pelayanan Pengisian Bahan Bakar Pertalite pada SPBU 54.832.12 di Kota Mataram Menggunakan Monte Carlo Termodifikasi - Afandi, Noval; Amrullah, Amrullah; Hikmah, Nurul; Kurniati, Nani (Mandalika Mathematics and Educations Journal, 2025)
PT. Pertamina (Persero) is one of the providers of refueling services in Indonesia. The role of Fuel Oil (BBM) is very important in people's lives, so to meet fuel needs, this company has built a Public Fuel Filling Station (SPBU). Petrol stations are a means to distribute fuel oil. As one of the companies that provide fuel in Indonesia, this company must pay attention to the quality of service. One of the strategic petrol stations in Mataram City is the petrol station 54.832.12 Jl. Gajah Mada Pagesangan, Mataram City. The large number of pertalite refueling during peak times in the morning and evening at this petrol station resulted in queues, so a study was carried out on the optimal condition of petrol station services based on the number of noozles using the Monte Carlo simulation method, by modifying the generation of random numbers using the Linear Congruent Method (LCM) random number generation. The simulation is carried out based on the arrival time and service time taken every 3 minutes 100 times. By conducting simulations 500 times and as many as 10 activities, optimal conditions were analyzed based on the number of noozles. The results obtained show that as many as 4 noozles are needed on the pertalite motorcycle dispenser to get optimal conditions because the average remaining queue is close to 1, which is 1.51 vehicles, and the Pertalite Car dispenser is enough with 1 noozle, the average remaining queue is close to 1, which is 1.62 vehicles.